2018
DOI: 10.1038/aps.2017.140
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells as a new therapeutic target for atherosclerosis

Abstract: Atherosclerosis is an autoimmune disease caused by self- and non-self-antigens contributing to excessive activation of T and B cell immune responses. These responses further aggravate vascular infiammation and promote progression of atherosclerosis and vulnerability to plaques via releasing pro-infiammatory cytokines. Regulatory T cells (Tregs) as the major immunoregulatory cells, in particular, induce and maintain immune homeostasis and tolerance by suppressing the immune responses of various cells such as T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 80 publications
1
74
0
3
Order By: Relevance
“…Taken together, these results as well as the increase in the vascular lipid deposition corroborate the literature, which has reported that TNF‐α is a potent inflammatory and pro‐atherosclerotic cytokine . Additionally, the anti‐atherogenic effects of IL‐10 have been previously demonstrated, so the decrease in that cytokine observed in our study could be an immune response promoted by stanozolol and could explain the observed results …”
Section: Discussionsupporting
confidence: 76%
“…Taken together, these results as well as the increase in the vascular lipid deposition corroborate the literature, which has reported that TNF‐α is a potent inflammatory and pro‐atherosclerotic cytokine . Additionally, the anti‐atherogenic effects of IL‐10 have been previously demonstrated, so the decrease in that cytokine observed in our study could be an immune response promoted by stanozolol and could explain the observed results …”
Section: Discussionsupporting
confidence: 76%
“…A study of elite Olympic athletes from various disciplines, found that athletes displayed higher frequencies of Tregs compared to age and sex-matched controls and this effect was associated with PA intensity ( Weinhold et al, 2016 ). Tregs release immunosuppressive cytokines like IL-10, IL-35, and TGF-β ( Olson et al, 2013 ), and decrease the production of pro-inflammatory cytokines like IFN-γ ( Mallat et al, 2003 ; Ou et al, 2018 ).…”
Section: Immune Cells and Physical Activitymentioning
confidence: 99%
“…Atherosclerosis is a chronic inflammatory disorder developed within the wall of large and mediumsized arteries and responsible for several adverse clinical events including acute coronary syndrome and ischemic stroke [1,2]. The disease is characterized by inflammatory infiltrates, subendothelial accumulation of oxidized lipids, angiogenesis and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Treg cells can also specifically express fork-head box P3 (FOXP3), a master regulator that is critical for their development and immunosuppressive function and is considered as one of the most reliable molecular markers for Treg cells [12,13]. Treg cells have been found to suppress atherosclerosis development or progression by down-regulating effector T cells (Teff)-mediated inflammatory response via multiple mechanisms, such as secretion of inhibitory cytokines interleukin (IL)10 (IL-10) and transforming growth factor beta (TGF-β) [1], cell-contact dependent suppression [14] and depletion of the IL-2 [15]. Several studies of experimental atherosclerosis showed that adoptive transfer of Treg cells prevented the development of atherosclerosis [16], while depletion of Treg cells by anti-CD25 antibody boosted the formation of atherosclerotic plaque [17].…”
Section: Introductionmentioning
confidence: 99%